Mutual coupling effects in 2×2 antenna array for ground penetrating radar on multilayered soil - Antonio Becerra-Pérez, Marco; Guerra-Huaranga, Tanith; Elisia Armas-Alvarado, Maria; Clemente-Arenas, Mark; Esther Rubio-Noriega, Ruth (Institute of Advanced Engineering and Science, 2024)
Caral stands as the Americas’ oldest city, boasting a heritage spanning 5,000 years. Over time, various natural forces have woven a complex geological stratum. To gain a deeper understanding of the Caral civilization, non-intrusive exploration methodologies like ground penetrating radar (GPR) are beginning to be used. This method safeguards the integrity of ancient subterranean remains. A GPR system is in development, tailored to the [200-500] MHz range, employing a 2×2 antenna array with dual polarization. These features enhance resolution without compromising penetration depth. However, using multiple antennas within complex, multi-layered environments introduce impedance band constraints and exacerbates antenna coupling issues. This study assesses the coupling of two antenna candidates: the Vivaldi with defected ground structures (DGS) and the log periodic dipole array (LPDA). The scattering parameters show that the LPDA antenna performed better considering measured and simulated data. Cross-polarization exhibited a broader bandwidth in the LPDA antenna, evident in both simulated and measured data. Additionally, a comprehensive comparison of GPR simulations for each antenna type within an 11-level multilayer medium, with different electromagnetic properties, further highlights LPDA. This antenna boasts a 209 MHz bandwidth and a coupling better than -23 dB for the cross-polarization configuration, firmly showing its best performance.